2022
DOI: 10.3390/en15145263
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Natural Gas, Oil, and Renewables Consumption on Carbon Dioxide Emissions: European Evidence

Abstract: Natural gas has returned to prominence in the agenda of European countries since the beginning of the invasion of Ukraine by Russia in 2022. However, natural gas is a fossil source with severe environmental implications. This paper aims to verify the impact of natural gas on carbon dioxide (CO2) emissions for a European panel from 1993 to 2018 for sixteen countries. An Autoregressive Distributed Lag (ARDL) model in the form of an unrestricted error correction model was used to identify the short-run impacts, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The environmental influence of oil usage was found to be more than natural gas. Belucio et al (2022) studied Europe from 1993–2018 by using ARDL. The authors stated that both oil and natural gas usage raised CO 2 emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The environmental influence of oil usage was found to be more than natural gas. Belucio et al (2022) studied Europe from 1993–2018 by using ARDL. The authors stated that both oil and natural gas usage raised CO 2 emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This supportive framework would help to create a stable investment framework that would encourage positive investment expectations, reduce uncertainty together with a lower investor’s sensitivity to the effect of unexpected events in their stock prices and returns, as shown in our study. Given the arising strategic importance of this type of energy in view of the critical geo-political events taking place during 2022 [ 63 , 64 ] it becomes clear the need of this institutional support.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Crow et al [10] found that decarbonizing the upstream component of the natural gas supply chain is achievable using carbon prices similar to those needed to decarbonize the energy system as a whole. Matheus Belucio et al [11] found that in the short-run, natural gas has a negligible impact on CO2 emissions when faced with oil consumption by verifying the impact of natural gas on carbon dioxide emissions for a European panel from 1993 to 2018 for sixteen countries.…”
Section: Introductionmentioning
confidence: 99%